2018
DOI: 10.1097/ico.0000000000001635
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical and Histological Characterization of Toxic Keratopathy From Depatuxizumab Mafodotin (ABT-414), an Antibody–Drug Conjugate

Abstract: ABT-414 accumulates in the basal corneal epithelium resulting in MEK due to increased apoptosis. Frequent lubrication and bandage contact lenses can provide symptom relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 8 publications
5
4
0
Order By: Relevance
“…However, similar descriptions and images of these slit lamp microscopy and IVCM findings have been reported in studies and case reports with other ADCs (see ''Literature Review of Corneal Changes with ADCs'' section for additional details) [13,[15][16][17][18][19][20].…”
Section: Description Of Mecs and Imaging Findingssupporting
confidence: 72%
See 4 more Smart Citations
“…However, similar descriptions and images of these slit lamp microscopy and IVCM findings have been reported in studies and case reports with other ADCs (see ''Literature Review of Corneal Changes with ADCs'' section for additional details) [13,[15][16][17][18][19][20].…”
Section: Description Of Mecs and Imaging Findingssupporting
confidence: 72%
“…A review of these 28 studies and case reports revealed that ADCs directed against other targets have also demonstrated a high incidence of ocular surface AEs. The terminology used to describe these events varied among reports; however, several of these terms (e.g., ''microcyst-like corneal epitheliopathy,'' ''microcystic epitheliopathy,'' ''corneal epithelial microcyst'') suggest these events have a microcyst-like presentation in the corneal epithelium, consistent with the MECs described here with belamaf treatment [16,22,23]. Ocular surface AEs observed with ADCs have typically been described as multiple, bilateral, microcyst-like lesions in the superficial cornea [17][18][19].…”
Section: Incidence and Descriptionsupporting
confidence: 61%
See 3 more Smart Citations